2017
DOI: 10.5194/acp-17-5477-2017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3-D thermal radiation on the development of a shallow cumulus cloud field

Abstract: Abstract. We investigate the effects of thermal radiation on cloud development in large-eddy simulations (LESs) with the UCLA-LES model. We investigate single convective clouds (driven by a warm bubble) at 50 m horizontal resolution and a large cumulus cloud field at 50 and 100 m horizontal resolutions. We compare the newly developed 3-D Neighboring Column Approximation with the independent column approximation and a simulation without radiation and their respective impact on clouds. Thermal radiation causes s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 69 publications
2
51
0
Order By: Relevance
“…The features of 3-D radiative transfer in the thermal spectral range are an increased cooling on cloud edges and a smoothed distribution of surfaces fluxes. While we compute thermal radiative transfer in a 3-D fashion, we expect these effects to be less important for this setup because feedbacks on the dynamics appear to happen only on longer timescales of a day (Klinger et al, 2017) and, more importantly, because it does not cause any asymmetries in the heating or cooling pattern.…”
Section: Les Modelmentioning
confidence: 99%
“…The features of 3-D radiative transfer in the thermal spectral range are an increased cooling on cloud edges and a smoothed distribution of surfaces fluxes. While we compute thermal radiative transfer in a 3-D fashion, we expect these effects to be less important for this setup because feedbacks on the dynamics appear to happen only on longer timescales of a day (Klinger et al, 2017) and, more importantly, because it does not cause any asymmetries in the heating or cooling pattern.…”
Section: Les Modelmentioning
confidence: 99%
“…For instance, the ventilation of the boundary layer humidity by shallow convective mixing can affect remotely the structure and strength of the intertropical convergence zone (Gregory, 1997;Neggers et al, 2007;Tiedtke et al, 1988). The longwave emission at shallow cloud tops as well as cold pools from precipitating cumuli impact the temperature and humidity distributions in the lower troposphere, which contribute to the mesoscale organization of shallow convection (Klinger et al, 2017;Naumann et al, 2019), but also to the transition to deep convection (Schlemmer & Hohenegger, 2014) and its aggregation (Coppin & Bony, 2015;Muller & Held, 2012). Therefore, advancing understanding of the key factors controlling (and interacting with) oceanic trade cumuli across a wide range of temporal and spatial scales, not only in models but also in observations, will certainly benefit to our understanding of climate as a whole and our ability to predict it.…”
Section: Introductionmentioning
confidence: 99%
“…Stephens et al, 1991;Barker et al, 2003a). While many have shown that differences between local and area-averaged fluxes produced by ICA and 3D RTMs can be large for some cloudy atmospheres (see several chapters in Marshak and Davis, 2005a), only a handful of CSRM experimental simulations have used 3D RT models interactively (Guan et al, 1997;Mechem et al, 2008;Jakub and Mayer, 2017;Klinger et al, 2017). It is widely recognized that the computational demands of 3D RTMs outweigh, for now at least, any scientific benefits they might afford, thereby amounting to (temporary) tacit acceptance of the ICA.…”
Section: Introductionmentioning
confidence: 99%